Perempuan dalam Konstruksi Sosial Religius Masyarakat Bali - Duana Sutika, I Nyoman (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 19 No 1 (2019), 2019)
Religious social construction in the life of society in Bali gives advantages for men but vice versa for women in all aspects of life. Social construction strengthens myths, creates discrimination, marginalization, and oppression of women. Religious interpretations are conducted in constructions created by patriarchal societies, so women are always positioned as subordinate status. This cultural and patriarchal ideology clarifies women as the second class after men, as oppressed objects in all living structures. The image of women behind this cultural manifestation has become a heritage that accepted by balinese people until recently although feminism's insistence has been done entirely to strive for the emancipation and equality in all aspects of life.